Final answer:
The inverse of the function f(x) = x^2 - 5 is found by swapping x and y and solving for y, resulting in y = ±√(x + 5). To ensure that the inverse is also a function, one must restrict the domain of the original function to non-negative values of x. Therefore, the inverse function, with the domain restricted, is f^{-1}(x) = √(x + 5).
Step-by-step explanation:
To find the inverse of the function f(x) = x^2 - 5, we need to swap the x and y and solve for y. Let's start by replacing f(x) with y:
Now we swap the variables:
Next, we solve for y:
- Add 5 to both sides: x + 5 = y^2
- Take the square root of both sides: y = ±√(x + 5)
However, since we need the inverse function to also be a function, it can have only one output for each input. The expression y = ±√(x + 5) implies two possible outputs for each input (one positive and one negative). To ensure that the inverse is a function, we must restrict the domain of the original function. For the function f(x) = x^2 - 5, if we restrict the domain to x ≥ 0, then the inverse will be:
Which is a function since for each x, there is only one possible y value. So, for f(x) = x^2 - 5 with x ≥ 0, the inverse function is f^{-1}(x) = √(x + 5), and it is a function.